2019
DOI: 10.1016/j.gca.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Mg isotope fractionation during continental weathering and low temperature carbonation of ultramafic rocks

Abstract: The Mg-isotope systematics of peridotite weathering and low-temperature carbonation have not yet been thoroughly investigated, despite their potential to provide insights into reaction pathways and mechanisms of lithosphere-hydrosphere transfer of Mg and sequestration of CO2 in carbonate minerals. Here, we present new observations of the evolution of Mg isotope ratios during subtropical ultramafic rock weathering and associated magnesite formation, including the lowest δ 26 Mg of magnesite reported so far. At … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 120 publications
1
33
1
Order By: Relevance
“…Following a molecular dynamics approach, Wang et al (2019) also concluded that lizardite crystallization preferentially removes 26 Mg from the fluid. These experimental results contrast with fractionation estimates based on natural samples that concluded that serpentinization does not fractionate Mg isotopes (Beinlich et al, 2014;Liu et al, 2017;Oskierski et al, 2019). Studies of natural samples also suggest that talc and Mg-rich clays formed during alteration are enriched in 26 Mg (Beinlich et al, 2014;Liu et al, 2017) in contrast with recent experimental studies that showed preferential incorporation of 24 Mg in stevensite and saponite (Hindshaw et al, 2020).…”
contrasting
confidence: 87%
See 1 more Smart Citation
“…Following a molecular dynamics approach, Wang et al (2019) also concluded that lizardite crystallization preferentially removes 26 Mg from the fluid. These experimental results contrast with fractionation estimates based on natural samples that concluded that serpentinization does not fractionate Mg isotopes (Beinlich et al, 2014;Liu et al, 2017;Oskierski et al, 2019). Studies of natural samples also suggest that talc and Mg-rich clays formed during alteration are enriched in 26 Mg (Beinlich et al, 2014;Liu et al, 2017) in contrast with recent experimental studies that showed preferential incorporation of 24 Mg in stevensite and saponite (Hindshaw et al, 2020).…”
contrasting
confidence: 87%
“… Bulk‐rock MgO/SiO 2 * vs. δ 26 Mg for Oman samples, abyssal peridotites (Liu et al., 2017) and serpentinite (Oskierski et al., 2019). Black solid line is mantle average and dashed black lines delineate the range of variability of mantle compositions (Teng, 2017; Teng et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mg has three stable isotopes of 24 Mg, 25 Mg, and 26 Mg. In general, magnesite minerals are depleted in 26 Mg compared with their source fluid, with the offset determined by a temperature‐dependent fractionation factor (de Obeso et al., 2020; Oskierski et al., 2019; Pearce et al., 2012). As such, the Mg isotope composition of carbonates can be used to trace the fluid/rock source of Mg (Tipper et al., 2006).…”
Section: Isotopic and Elemental Constraints On Magnesium Carbonate Formationmentioning
confidence: 99%
“…This agrees with previous descriptions of the bedrock lithologies and mineralogy at Woodsreef (Glen and Butt, 1981;O'Hanley and Offler, 1992). The nodular bedrock carbonate from the mine pit consists of magnesite, with traces of lizardite and associated pyroaurite (WOMP-M1; Oskierski et al, 2019). Lizardite dominates the bulk tailings sample (WO-T2top) but trace amounts of pyroaurite, magnetite, quartz and hydromagnesite are present.…”
Section: Mineralogymentioning
confidence: 99%
“…Teng et al, 2007;Yang et al, 2009;Teng et al, 2010). Similarly, the Mg isotopic composition of bulk peridotite, and of primary minerals in peridotite, is not significantly affected by serpentinisation but by weathering and hydrothermal carbonate alteration (Beinlich et al, 2014;Liu et al, 2017;Oelkers et al, 2019;Oskierski et al, 2019). As demonstrated by Oelkers et al, (2019) for injection of CO2bearing fluids into basalt, Mg isotopic compositions can thus be used to assess the fate of Mg during weathering and carbonation reactions.…”
Section: Introductionmentioning
confidence: 99%